2017
DOI: 10.1186/s13731-017-0062-3
|View full text |Cite
|
Sign up to set email alerts
|

Leadership in innovation projects: an illustration of the reflective practitioner and the relation to organizational learning

Abstract: The purpose of this conceptual article is to demonstrate that Donald Schön's Reflective Practitioner actually outlines an explicit model of the steps that project leaders in practice apply largely unaware. This reflective research model furthermore can be meaningfully combined with Argyris and Schön's model of organizational learning. The combined research and learning model can support project team members and leaders to enhance their reflectiveness and improve their project success. Eighteen project leaders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…From this research, we conclude as well that certain organizational aspects of WI as defined by innovation behavior are important for successful implementation of innovation. Employee engagement is an essential driver of WI ( Oeij et al, 2017 ). At the organizational level, the results revealed that organizational factors have different impacts on innovation climate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From this research, we conclude as well that certain organizational aspects of WI as defined by innovation behavior are important for successful implementation of innovation. Employee engagement is an essential driver of WI ( Oeij et al, 2017 ). At the organizational level, the results revealed that organizational factors have different impacts on innovation climate.…”
Section: Discussionmentioning
confidence: 99%
“…This means that the management should engage, stimulate and support the team apart from just suggesting ideas. Then, employees will have the opportunity to suggest in what way the ideas could be developed based on their expertise and point of view ( Oeij et al, 2017 ) ( Totterdill and Exton, 2017 ). The challenge now is to bridge the gap between employees and management for WI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe the approaches of Leadership (Yukl, 2012;Oeij, Gaspersz, Van Vuuren & Dhondt 2017) and Workplace innovation (De Sitter, den Hertog & Dankbaar 1997;Pot, Rus & Oeij, 2017) may help to understand the relationship between employee and organisational factors, and innovation adoption. Workplace innovation focuses on organisation of work as a form of innovation and employee participation, with the objective of improving both quality of work and organisational performance (Pot, Rus & Oeij 2017).…”
Section: Introductionmentioning
confidence: 99%
“…(Raelin, 2007) Oeij et al argue that "Donald Schon's reflective practitioner actually outlines an explicit model of the steps that project leaders in practice apply largely unaware" and illustrates with examples of leadership in innovation projects. (Oeij et al, 2017).…”
Section: Relevant Literature Concerning Internships and Innovation Mamentioning
confidence: 99%